Clinical Characteristics and Influencing Factors of Esophageal Squamous Cell Carcinoma Patients with Brain Metastases and Their Influence on Survival - LUO Huachun; FU Zhichao; FENG Jing; SHEN Zhiyong; YING Wenmin; CAI Lyujuan; CHENG Huihua (Zhongliu Fangzhi Yanjiu, 2020)
Objective To investigate the clinical characteristics and influencing factors of patients with brain metastases from esophageal squamous cell carcinoma (BM-ESCC) and their impact on survival. Methods We retrospectively analyzed the clinical data of 67 patients with newly diagnosed BM-ESCC from December 2000 to December 2016 in our hospital, to analyze the correlation of brain metastases with clinicopathological characteristics and the survival. Results The number of BM-ESCC was positively correlated with T and N stages (P < 0.05). The median survival time was 9.65 months. Logistic regression analysis showed that N2 and N3 were risk factors for brain metastasis in patients with esophageal squamous cell carcinoma, and the risk of brain metastasis in patients with N0 and N1 was lower (P < 0.05). Log rank survival analysis reveal that patients with one brain metastasis had a significantly longer survial than those with two and three brain metastasis (P < 0.05); patients with N0+N1 stage had better prognosis than those with N2 and N3 (P < 0.05). Cox regression model showed that T3+T4 stage, N3 stage and whole brain radiotherapy were independent prognostic factors for BM-ESCC patients (P < 0.05). Conclusion In esophageal squamous cell carcinoma patients with brain metastases, the number of brain metastases is positively correlated with T and N stages; the higher N stage is, the higher the risk of brain metastases is; the higher T and N stages are, the worse the prognosis is; whole brain radiotherapy could offer better survival benefits.